Marka jako nośnik wizerunku kraju pochodzenia — Rosja w narracji marketingowej Moscow Centre of SPARC Technologies o marce Elbrus - Kokowicz, Dorota (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The author of this article demonstrates how the Moscow Centre of SPARC Technologies (MCST) communicates on Russian computer brand Elbrus and at the same time — how this brand becomes a carrier of image of its country of origin: Russia. The author also presents the results of the content analysis of the MCST’s website in order to show what image of Russia emerges from marketing narration about the brand, full of references to current political situation of Russia and its history.
Keywords: country-of-origin effect; image of Russia; nation brand; nation branding; brands as communication channels